2017
DOI: 10.18805/ijar.v0iof.9148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of former acquaintance on aggression, lesion and growth performance in weaned piglets after mixing

Abstract: Excessive aggression between weaned piglets after mixing is a welfare and production issue resulting in stress, injuries and economic losses. The aim of this study is to determine the effect of former acquaintance (FA) on aggression, lesion and growth performance in weaned, mixed piglets. The results showed that the FA group significantly reduced the number of fights, time spent fighting, number of bullying events, lesions, the average injury scores of the front site and middle site of weaned piglets after mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These stressors lead to a reduced growth performance, feed intake reduction, maldigestion and absorption (Lallès et al, 2004) which can result in economic losses. Many corrective measures, such as raising management (Mei and Gan 2018), nutritional management and feed supplementation (Namted et al, 2020) were studied. Previous studies on fermented potato protein (FPP) supplementation in suckling pigs were showed to increase serum IGF-1 level (Poltep et al, 2016), decrease mortality rate at 24 h of age (Kummer et al, 2015) and increase IGF1 expression in peripheral white blood cell (Poltep et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These stressors lead to a reduced growth performance, feed intake reduction, maldigestion and absorption (Lallès et al, 2004) which can result in economic losses. Many corrective measures, such as raising management (Mei and Gan 2018), nutritional management and feed supplementation (Namted et al, 2020) were studied. Previous studies on fermented potato protein (FPP) supplementation in suckling pigs were showed to increase serum IGF-1 level (Poltep et al, 2016), decrease mortality rate at 24 h of age (Kummer et al, 2015) and increase IGF1 expression in peripheral white blood cell (Poltep et al, 2016).…”
Section: Introductionmentioning
confidence: 99%